KADAR VITAMIN D TERHADAP DERAJAT LUKA PADA PASIEN DIABETES MELITUS - Ajeng Pratiwi; Suriadi; Kharisma Pratama; Syahid Amrullah; Jaka Pradika (Jurnal Riset Keperawatan dan Kesehatan, 2025)
Background: Diabetes Mellitus (DM) is a chronic metabolic disease characterized by elevated blood glucose levels, which over time causes serious damage to the heart, blood vessels, eyes, kidneys, and nerves. Vitamin D is thought to affect glucose metabolism, reduce ß-cell function, and increase insulin resistance and glucose intolerance. Objective: This study aimed to determine the relationship between vitamin D levels and the degree of wounds in patients with diabetes mellitus at the Kitamura Clinic, Pontianak. Methods: This research method is a quantitative descriptive method. Results: This study showed that the majority of patients with diabetic foot ulcers at the Kitamura Clinic Pontianak had normal vitamin D levels (86.7%), while 10% had low levels, and 3.3% had high levels. Most of the wounds were at a severe level, namely grade 3 (33.3%) and 4 (30%). Spearman correlation analysis showed a negative relationship between vitamin D levels and wound severity (r = -0.267), but this relationship was not statistically significant (p = 0.153). Conclusion: This study concluded that vitamin D levels were not significantly associated with the severity of diabetic foot ulcers.